The Application of Synchronization Methods Using Prostaglandin F 2ï¡,by Intra Vaginal Sponges (IVS) and Intra Muscular (IM) to Improve Reproductive Performance of Thintailed Ewe Lambs - Saoeni, R (ANIMAL PRODUCTION, 2007)
The purpose of the experiment was to investigate the effect of different administration method of PGF2a, i.e. intra vaginal sponges (IVS) and intra muscular (IM) on the onset and the duration of estrus, and Non-return Rate (NR) in thin tailed ewe lambs. A total of 20 thin tailed ewe lambs, aged 12-15 months, were at random assigned to one of four treatment groups in Completely Randomized Designed (CRD) : Animals in Treatment group I (P1) received PGF2a of 5 mg/ml/head intramuscularly ; Treatment group II (P2) received PGF2a of 5 mg/ml/head by intra vaginal sponges for twodays;Treatment groupIII(P3) received PGF2a of 5 mg/ml/head by intra vaginal sponges for four days; Treatment group IV (P4) received PGF2a of 5 mg/ml/head by intra vaginal sponges for six days. Two rams, aged 2-2.5 years used as a mated. Each treatment was repeated five times. Variables measured were onset and duration of estrus, and Non-return Rate (NR) in 30 days. Collected data were analyzed using analysis of variance followed by Post-hoc of Least Significant Difference (LSD). Average values of onset of estrus for P1, P2, P3 and P4 were 22.91, 23.16, 26.31 and 44.57 hours, respectively. Average values of duration of estrus for P1, P2, P3 and P4 were 26.36, 48.36, 94.65 and 146.56 hours, respectively. Analysis of variance indicated that the administration method of PGF2a affected significantly (P<0.01) on the onset and the duration of estrus. Non-return Rate (NR) in 30 days for P1, P2, P3 and P4 was 100,100, 20 and 20 percent, respectively. In conclusion, the application of estrous induction methods using Prostaglandin F2a by intra vaginal sponges (IVS) for two days and intra muscular (IM) can improve reproductive parameters of thin tailed ewe lambs. (Animal Production 9(2): 129-134 (2007) Key Words: Prostaglandin estrous, Non-return Rate, sheep